Costanzo Physiology - Costanzo, Linda S. (Elsevier, 2022)
Through six highly regarded editions, students and instructors alike have come to appreciate Dr. Linda Costanzo's clear, helpful writing style, logical organization, and easy-to-follow presentation of a challenging and complex topic in medical education. Costanzo Physiology, 7th Edition, retains the step-by-step, to-the-point approach that makes this text ideal for coursework and USMLE preparation. Complex concepts are presented in a simple, easy-to-digest manner, and are accompanied by well-designed figures and tables that provide handy visuals for procedures or physiologic equations. Fully updated throughout, this edition remains the students' choice for concise, clear instruction and a strong foundation in human physiology.